PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNINGUNTUK MENINGKATKAN HASIL BELAJAR PPKnSISWA KELAS VI SD NEGERI 014 BERINGIN MAKMURKECAMATAN KERUMUTAN - Dirto ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes PPKn. This is evidenced by the acquisition of the average value obtained PPKn learning outcomes of students is 50.00. The percentage of students who achieve KKM only 11 students (39.28%) and that did not reach the KKM is 17 students (60.71%). This research is a class act who do as much as two cycles. Collecting data in this study are engineering achievement test PPKn. The results showed that the application of contextual approach teacing and learning can improve learning outcomes PPKn. This is evidenced by the thoroughness of learning outcomes in indiviu students each cycle has increased. At the base score is the number of students who completed 11 students or 39.28%, and who did not complete as many as 17 students or 60.71%. In the first cycle of increasing that number of students who completed by 16 students or 57.14%, and who did not complete as many as 12 students or 42.85%. In the second cycle the number of students who pass an increase of 23 students or 82.14%, and who did not complete as many as five students or 17.85%.